Study on consumer decision making styles in Kota Kinabalu, Sabah: Multi product analysis - Janeta Anthony @ Janet (2004)
Consumers use a variety of decision-making styles. Decision making is more complex and even more important for consumers today than in the past. Consumers are besieged by advertising, news article and direct mailings that provide an abundance of information, much of it with mixed messages. In addition, increases in the number and variety of goods, stores and shopping malls and the availability of multi component products and electronic purchasing capabilities have broadened the sphere for consumer choice and have broadened the sphere for consumer choice and have complicated decision making. This study investigates the various decision making styles and to what extent these dimensions influence consumers purchase intentions. The six dimensions of decision making styles are the quality and perfectionism consciousness, brand consciousness, impulsive, novelty fashion consciousness, confuse from over-choice and habitual brand loyalty. Two types of consumer product namely the shopping product (clothing) and specialty product (wrist-watch) were used as the leading product for purchase intention. The findings conclude that there is significant relationship between decision making styles to consumer purchase intention to shopping product and specialty product. However, only quality and novelty fashion influence the purchase intention to clothing. As for the purchase intention to wrist-watch, quality, novelty and confuse from over-choice will also influence the purchases. The findings also conclude that age does not moderate the relationship between decision-making style and purchase intention. In contrary, income does moderate the relationship between brand consciousness and purchase intention to wrist-watch.